Analisis Perancangan Sistem Helpdesk menggunakan Prototype dan ISO 25010 pada PT Teknologi Informatika Solusindo - Dandi Fajar ismail; Miftaqudin Miftaqudin; Chairul Anwar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid development of information technology has encouraged organizations to improve the quality of information technology services in order to support the effectiveness and efficiency of business processes. PT Teknologi Informatika Solusindo, as a company engaged in information technology services, faces several challenges in managing helpdesk services, including manual ticket recording, delays in handling user complaints, difficulties in monitoring problem resolution status, and a lack of transparency in service processes. These issues have the potential to reduce service quality and user satisfaction. This study aims to analyze and design a web-based helpdesk system that can improve report management effectiveness, accelerate problem resolution processes, and provide more accurate and integrated service information. The system development method used is the Prototype model because it facilitates continuous communication and evaluation with users, resulting in a system that better meets organizational requirements. Furthermore, software quality testing is conducted based on the ISO 25010 standard to ensure that the system satisfies quality aspects such as functional suitability, usability, reliability, performance efficiency, security, compatibility, and maintainability. The results of this study indicate that the designed web-based helpdesk system simplifies ticket management, improves service response time, facilitates monitoring activities, and supports decision-making through structured and well-documented information. Therefore, the developed system can serve as an effective solution for improving the quality of information technology services at PT Teknologi Informatika Solusindo.